Pengaruh Metode Imla’ untuk Meningkatkan Keterampilan Menulis Bahasa Arab (Maharah Kitabah) Siswa Kelas VII MTs Masyariqul Anwar Caringin - Nabilah, Rahma; Ussyafiqoh, Fitria Nisa; Jannah, Kholisah Hisbiatul; Indriana, Dina; Hidayat, Wahyu (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this research is to examine how the use of the imla' method influences the writing skills (maharah kitabah) of seventh-grade students at MTs Masyariqul Anwar. Twenty students served as the sample for this study, which employed a quantitative methodology. Data were collected through tests, observations, and documentation and were subsequently analyzed using the product-moment correlation formula. With a correlation coefficient of 0.72, the findings indicate a strong relationship between students' writing skills and the imla' approach. In other words, the use of this approach contributed 72% to the improvement in writing skills. The average score for students' overall writing ability was 77.3, which is considered high, while their average score for imla' was 75. This study highlights the value of the imla' method as an effective strategy for improving the writing proficiency of madrasah-level students in Arabic.